2021
DOI: 10.3389/fpsyt.2021.739823
|View full text |Cite
|
Sign up to set email alerts
|

Time-Specific Associations of Tumor Necrosis Factor-α Levels and Polymorphisms (−850 C/T or −308 G/A) With Suicidal Ideation in Acute Coronary Syndrome Patients

Abstract: Background: Considering the association of inflammation with suicide and acute coronary syndrome (ACS), we investigated the individual and interactive effects of serum tumor necrosis factor-alpha (sTNFα) levels and two polymorphisms (−850 C/T and −308 G/A) on suicidal ideation (SI) after ACS.Methods: The SI status using items on the Montgomery–Åsberg Depression Rating Scale (MADRS), related covariates including sociodemographic and clinical characteristics, sTNFα levels, and tumor necrosis factor-alpha (TNF-α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…33 So, in the case of ACS, the level of TNF-α increased within two weeks after the onset and increased the serum level expression around one year after onset. 34 This is because of the duration of a statins prescription required to decrease TNF-α is from 12 weeks up to 6 months or more, depending on the types of statins and level of lipid profile, 35,36 however, our follow up in this study was only after 1 month.…”
Section: Discussionmentioning
confidence: 95%
“…33 So, in the case of ACS, the level of TNF-α increased within two weeks after the onset and increased the serum level expression around one year after onset. 34 This is because of the duration of a statins prescription required to decrease TNF-α is from 12 weeks up to 6 months or more, depending on the types of statins and level of lipid profile, 35,36 however, our follow up in this study was only after 1 month.…”
Section: Discussionmentioning
confidence: 95%
“…In the second study, SI was associated with the -850 (C/T + T/T) genotype of rs1799724 polymorphism only within the first 2 weeks. The authors also found a significant interaction of -308 G/A and -850 C/T polymorphisms on SI at 1 year after ACS (40). Wang et al (41) studied three polymorphisms, rs361525, rs1800629, and rs1799964, in a post-mortem sample (SCs and controls).…”
Section: Pro-and Anti-inflammatory Cytokines Tnfαmentioning
confidence: 98%
“…They reported that the G allele was more 10.3389/fpsyt.2022.1003034 frequent among SAs having made a single attempt compared to controls (38). Kang et al (39,40) conducted two studies on the same cohort to investigate the relationship of SI to TNFα polymorphisms 2 weeks and 1 year after an acute coronary syndrome (ACS). In the first study, a significant association between SI and the -308A allele was found during the acute phase (2 weeks) but it did not persist at the end of follow-up or after Bonferroni correction (39).…”
Section: Pro-and Anti-inflammatory Cytokines Tnfαmentioning
confidence: 99%